The The relationship of accessibility, ownership of health security and family support with the behavior of III trimester pregnant women in choosing a delivery help - Mayanti, Rini Rinda; Lisdayani, Ane; Hasanah, Noor; Susilawati, Emalia; Rahayu, Lusi Ginanjar; Novitasari, Lia; Hanifah, Fanni; Hidayani, Hidayani (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: One of the aspects that causes the high MMR in Indonesia and in several regions is that the coverage of assistance by health workers is still low. The reason why people decide to give birth to non-health workers (quacks) is because of the low level of education in society, culture, and the economy. Factors that influence the choice of birth attendants include areas where coverage is still not close to health facilities, ownership of health insurance, and family support, which is still the predominant reason mothers do not choose birth attendants by professionals in health facilities. Objective: The general aim of this research is to understand the relationship between accessibility and ownership. Health insurance and family support with the behavior of TMT III pregnant women in choosing birth attendants. Methods: This research method is quantitative research with a cross-sectional design.Result: The chi-square test results show a relationship between accessibility, ownership of health insurance, family support, and the behavior of TMT III pregnant women in choosing birth attendants. Result: The chi-square test results show a relationship between accessibility, ownership of health insurance, family support, and the behavior of TMT III pregnant women in choosing birth attendants. Conclusion: It is hoped that this can increase the role of the community in helping all mothers who are about to give birth to choose professional health workers to assist them in giving birth so that it is hoped that all mothers in labor can be assisted in giving birth through a safe delivery process so that the mother and baby are healthy and safe.